Estudio de las estrategias comunicacionales turísticas llevadas a cabo por el Gobierno Autónomo Descentralizado parroquial de Veracruz, cantón Pastaza, provincia de Pastaza y su incidencia en el desarrollo local del sector. Período septiembre 2013 abril 2014. Propuesta alternativa - Jiménez Jiménez, Carmen Crimilda (2015)
To, 7 km south-east of the canton and the province of Pastaza, road to Macas, the Veracruz parish, whose name is in honor of the Republic of Mexico, who supported Ecuador in the confrontation with Peru in 1941 is . It is a place rich in biodiversity of flora, fauna and cultural events, the dense forest with the extraordinary wealth of fine woods, plants and shrubs enriched water resources; rivers, streams and waterfalls Veracruz have made an ideal setting for recreation and leisure tourist. The ploblemática research work is framed in the absence of a study of the tourist sites and strategies for dissemination, which limits the possibilities of local development of Veracruz parish. The authorities of the Autonomous Government of Veracruz Descetralizado not have communication strategies and with a visionary plan where investment projects are implemented to exploit and publicize tourism. The purpose of this research is to find appropriate means to promote tourist attractions contributing to the development of the sector. It had as general objective: to contribute through audiovisual communication strategies for the work of parish Decentralized Autonomous Government of Veracruz in order to promote the socioeconomic development of the sector, as the bank only has promoted through posters, brochures, memorandums and crafts all work carried out, giving tourist and cultural riches minimal space. This investigation led to propose an alternative proposal to fill the gap.